Waqf and Its Implementation in Islamic Education: A Comparative Study of Educational Waqf in Indonesia and Thailand from the Perspective of Islamic Law - Moh. Mahrus; Imroh Atul Musfiroh; Galby Silvia Rachmah (SYAMIL: Journal of Islamic Education, 2024)
This study aims to analyze the application of waqf in the field of education in Indonesia and Thailand from the perspective of Islamic law. Waqf, as a socio-economic instrument in Islam, has played an important role in the development of the education sector in various countries. This research discusses how waqf is used to fund educational institutions, both in the form of land, buildings, and endowment funds, as well as the challenges and opportunities that arise in its implementation. Using a qualitative approach, this study compares the practice of educational waqf in Indonesia and Thailand, two countries with significant Muslim populations but with different education systems. The results of the study show that although the two countries have great potential to optimize waqf in the education sector, there are some differences in its management and utilization, which are influenced by local legal, regulatory, and cultural factors. This research also identifies the important role of religious institutions and the government in supporting the sustainability of educational waqf. The conclusions of this study highlight the importance of regulatory reform and increasing public understanding of waqf to maximize its impact in improving access and quality of education in both countries.